Selective dry cow therapy: Clinical field trial on prevention and cure of intramammary infections - R.E. Niemi; M. Hovinen; P.J. Rajala-Schultz (Journal of Dairy Science)
ABSTRACT: Intramammary antibiotic dry cow therapy (DCT) at the end of lactation is a key measure in the management and control of bovine mastitis. Currently, livestock production is under pressure to reduce antibiotic consumption, emphasizing the need to avoid medicating all cows at dry-off, and instead treat only infected cows. The study objective was to evaluate IMI cure risk, new IMI risk, and postcalving IMI risk between DCT-treated and untreated quarters over the dry period. The sample totaled 269 cows from 12 Finnish automatic milking system herds entering the dry period between 2019 and 2021. Cows eligible for the study had a final DHI test-day SCC ≥100,000 cells/mL and had no clinical signs of mastitis. Based on odd or even identification numbers, cows with an SCC between 100,000 and 250,000 cells/mL were sequentially assigned to either receive DCT at dry-off (DCT100–250) or remain untreated (NoDCT100–250). All cows with an SCC >250,000 cells/mL received DCT (DCT>250). No quarters received teat sealants. Farmers collected aseptic quarter milk samples for microbiological quantitative real-time PCR analysis 0 to 4 d before dry-off and 0 to 4 d after calving. The outcome of the statistical model was the odds of a quarter having an IMI at freshening 0 to 4 d after calving. The statistical tool was a generalized linear mixed-effects model with logit link function and 2-level random intercepts, cows nested within herds. Quarter-level IMI prevalence at dry-off was 17.6% (45/256) for NoDCT100–250, 22.2% (83/374) for DCT100–250, and 32.0% (132/413) for DCT>250. Quarter-level IMI prevalence at freshening was 36.2% (84/232) for NoDCT100–250, 13.6% (50/369) for DCT100–250, and 11.6% (46/397) for DCT>250. The untreated quarters in the NoDCT100–250 group had a 1.1 times higher risk of failing to cure over the dry period than the treated quarters in the DCT100–250 group (unadjusted risk ratio [RR] 1.10, 95% CI 0.94–1.28) and a 1.2 times higher risk than the treated quarters in the DCT>250 group (unadjusted RR 1.15, 95% CI 1.00–1.33). The untreated quarters in the NoDCT100–250 group had a 1.5 times higher risk of having a new IMI over the dry period than did the treated quarters in the DCT100–250 group (unadjusted RR 1.48, 95% CI 1.35–1.63) and a 1.4 times higher risk than the treated quarters in the DCT>250 group (unadjusted RR 1.35, 95% CI 1.23–1.49). The principal cause of new IMI was NAS, followed by Streptococcus dysgalactiae. Quarters in the NoDCT100–250 group had 6.6 times higher odds for having an IMI at freshening than did quarters in the DCT100–250 group (95% CI 3.52–12.21). According to our findings within the framework of this experiment, selectively DCT-treated cows with an SCC between 100,000 and 250,000 cells/mL at dry-off demonstrated that, although the group-specific cure risks over the dry period were high, untreated quarters had a higher risk of acquiring a new IMI over the dry period than did treated quarters, highlighting the effectiveness of DCT in reducing IMI risks. The prophylactic use of antibiotics, however, is not recommended, and in some countries is even prohibited.